Apigenin Provides Structural Protection to Human Fibrinogen against Nitrosative Stress: Biochemical and Molecular Insights - Aisha Farhana; Abdullah Alsrhani; Yusuf Saleem Khan; Mohammad Salahuddin; Mohammed Ubaidullah Sayeed; Zafar Rasheed (Biomolecules, 2024)
Background: Peroxynitrite (ONOO−) is an oxidant linked with several human pathologies. Apigenin, a natural flavonoid known for its health benefits, remains unexplored in relation to ONOO− effects. This study investigated the potential of apigenin to structurally protect fibrinogen, an essential blood clotting factor, from ONOO−-induced damage. Methods: Multi-approach analyses were carried out where fibrinogen was exposed to ONOO− generation while testing the efficacy of apigenin. The role of apigenin against ONOO−-induced modifications in fibrinogen was investigated using UV spectroscopy, tryptophan or tyrosine fluorescence, protein hydrophobicity, carbonylation, and electrophoretic analyses. Results: The findings demonstrate that apigenin significantly inhibits ONOO−-induced oxidative damage in fibrinogen. ONOO− caused reduced UV absorption, which was reversed by apigenin treatment. Moreover, ONOO− diminished tryptophan and tyrosine fluorescence, which was effectively restored by apigenin treatment. Apigenin also reduced the hydrophobicity of ONOO−-damaged fibrinogen. Moreover, apigenin exhibited protective effects against ONOO−-induced protein carbonylation. SDS-PAGE analyses revealed that ONOO−treatment eliminated bands corresponding to fibrinogen polypeptide chains Aα and γ, while apigenin preserved these changes. Conclusions: This study highlights, for the first time, the role of apigenin in structural protection of human fibrinogen against peroxynitrite-induced nitrosative damage. Our data indicate that apigenin offers structural protection to all three polypeptide chains (Aα, Bβ, and γ) of human fibrinogen. Specifically, apigenin prevents the dislocation or breakdown of the amino acids tryptophan, tyrosine, lysine, arginine, proline, and threonine and also prevents the exposure of hydrophobic sites in fibrinogen induced by ONOO−.